2021
DOI: 10.1016/j.memsci.2020.118752
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient preparation of Ce0.8Sm0.2O2-δ–SrCo0.9Nb0.1O3-δ dual-phase four-channel hollow fiber membrane via one-step thermal processing approach

Abstract: Fabricating dual-phase hollow-fiber membranes via a one-step thermal processing (OSTP) approach is challenging, because of complex sintering kinetics and the subsequent impacts on membrane morphology, phase stability, and permeation properties. In this study, we have demonstrated that Ce 0.8 Sm 0.2 O 2-δ -SrCo 0.9 Nb 0.1 O 3-δ (SDC-SCN) four-channel hollow fiber membrane can be manufactured via a single high-temperature sintering process, by using metal oxides and carbonates directly as membrane materials (sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…With the sintering temperature was increased from 1400 to 1500 C, it can be observed that the porosity of the BCYC0 hollow fiber membrane decreases 3C,D, all the channels were complete and crack-free. White dots which were commonly observed in hollow fibers fabricated via the OSTP, [29][30][31] were observed on the inner surface of the hollow fiber. The preparation of hollow fiber membranes via the OSTP involved organic combustion and perovskite oxide synthesis, which requires the participation of oxygen.…”
Section: Morphologiesmentioning
confidence: 95%
See 3 more Smart Citations
“…With the sintering temperature was increased from 1400 to 1500 C, it can be observed that the porosity of the BCYC0 hollow fiber membrane decreases 3C,D, all the channels were complete and crack-free. White dots which were commonly observed in hollow fibers fabricated via the OSTP, [29][30][31] were observed on the inner surface of the hollow fiber. The preparation of hollow fiber membranes via the OSTP involved organic combustion and perovskite oxide synthesis, which requires the participation of oxygen.…”
Section: Morphologiesmentioning
confidence: 95%
“…The perovskite hollow fibers were obtained via a single‐step thermal processing, which accomplishes the in situ conversion of the raw chemicals into perovskite oxides. The OSTP approach was expected to avoid grain overgrowth and reduce the densification temperature 31 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, for the perovskite phase, the grain boundary with higher energy often leads to phase transition and weakens the stability. Zhang group [42] and Yang group [43] added nanoparticles to the grain boundary to restrain the phase transition and prepared stable dual-phase Ce 0.8 Sm 0.2 O 2−δ -SrCo 0.9 Nb 0.1 O 3−δ and Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3−δ OTM, respectively. For our OTMs, there are no similar structures in the grain boundary.…”
Section: Surface Morphology Characterizationmentioning
confidence: 99%